A comparative analysis of methods and applications for automated model generation in architectural design for building renovation processes (Architecture Image Studies, 2024)
Rehabilitating existing structures offers a chance to modify the layout to fulfill facility requirements and achieve sustainability in the built setting at high utilization rates and minimal expense. The design for construction renovations is intricate, and executing architectural design plans manually requires enhanced efficiency and general resilience. Computation optimization enables Automated Architectural Design (AAD) to effectively facilitate building refurbishment by making decisions grounded in performance evaluations. This study thoroughly examines the present research situation of AAD and offers a cutting-edge overview of the application of AAD methods to building rehabilitation. The deficiencies and prerequisites of employing AAD for building rehabilitation are examined from qualitative and quantitative perspectives, offering insights for future study. The research indicates that much effort remains to implement AAD in building rehabilitation, encompassing the rapid acquisition of input information, broadening optimization subjects, adopting designing methodologies, and enhancing workflow and productivity.